2007
DOI: 10.1177/0115426507022005494
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Obesity: A Weighty Issue Affecting Transplant Candidacy and Outcomes

Abstract: Because of the global increase in prevalence of obesity, many more overweight and obese individuals are undergoing evaluation for transplantation than in the past. Although obesity seems to provide a survival benefit in dialysis patients, obesity has traditionally been considered a contraindication for transplantation of most organs. It is theorized that obesity will contribute to worse transplant outcomes, including lower rates of graft and patient survival and higher rates of delayed graft function and infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The national secular trend toward overweight and obesity extends to patients with ESRD who are seeking kidney transplantation, resulting in higher body weight before transplant and thereby increasing the risk of NODAT(12). In fact, in the U.S., the prevalence of obesity (BMI ≥30 kg/m 2 ) among transplant recipients at the time of kidney transplantation doubled between 1987 and 2001 (13). Thus, a higher number of obese patients receiving transplants, now and in the future, may contribute to growth in the incidence rate of NODAT.…”
Section: Clinical and Economic Significance Of Nodatmentioning
confidence: 99%
See 1 more Smart Citation
“…The national secular trend toward overweight and obesity extends to patients with ESRD who are seeking kidney transplantation, resulting in higher body weight before transplant and thereby increasing the risk of NODAT(12). In fact, in the U.S., the prevalence of obesity (BMI ≥30 kg/m 2 ) among transplant recipients at the time of kidney transplantation doubled between 1987 and 2001 (13). Thus, a higher number of obese patients receiving transplants, now and in the future, may contribute to growth in the incidence rate of NODAT.…”
Section: Clinical and Economic Significance Of Nodatmentioning
confidence: 99%
“…Type 2 diabetes mellitus and NODAT share similar risk factors, especially obesity. The prevalence of obesity (BMI ≥30 kg/m 2 ) at the time of transplantation among transplant recipients in the U.S. has doubled between 1987 and 2001 (13). Because higher BMI before transplant correlates with insulin resistance after transplantation, obesity treatment seems to be reasonable target for intervention.…”
Section: Lifestyle Interventions To Prevent Diabetesmentioning
confidence: 99%
“…Obese individuals have larger absolute lean body and fat masses than non-obese individuals of the same age, gender and height, which might lead to altered pharmacokinetics of chemotherapeutic agents [1]. Although obesity seems to provide a survival benefit in dialysis patients, obesity has traditionally been considered a contraindication for transplantation of both bone marrow transplant recipients as well as solid organ transplants [2]. It was widely adopted that obesity will contribute to worse transplant outcomes, including lower rates of engraftment and patient survival and higher rates of delayed graft function and infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…This seemingly paradoxical finding may be because their body fat was retained while muscle atrophy was occurring. Many transplant centers defer patients from transplant listing until BMI is less than 35 because of comorbidities associated as diabetes [24]. The United Network for Organ Sharing provided data has shown that, in the past decade, the obesity-associated liver disease has become an increasing indication for transplantation.…”
Section: Prevalence Of Malnutrition In Patients With Advanced Liver Dmentioning
confidence: 99%